The role of fatigue during the phases of the vertical jump in young football players - Sannicandro, I.; Petito, A.; Rosa Rosa, A.; Piccinno, A.; de Pascalis, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The analysis of the vertical jump phases becomes relevant in consideration of the epidemiological data of non-contact muscular and joint traumas. Such data have shown that non-contact traumas in team sports constitute 39% of injuries in female basketball and 14% of injuries in men`s football (Junge et al., 2006) Thus, the assessment of the vertical jump is not only a control indicator of performance and efficiency of the neuromuscular system of athletes, but it can also be analysed from the qualitative point of view. The aim of the study was to investigate the influence of fatigue upon various phases of the vertical jump after a maximal aerobic power test. Methods The sample was formed of n=15 young professional football players (mean±SD age, height and weight: 13.7±0.4 years, 166.1±6.1 cm, 58.7±4.7 Kg respectively). The Counter Movement Jump (CMJ) was used to evaluate vertical jump phases by means of two different dynamometric platforms, one for each limb (Twin Plates and Globus Italia), equipped with specific software for the analysis of the movement. The evaluation of the jump was carried out before and immediately after the execution of an incremental shuttle run test (Léger & Cazorla, 1993). Statistical analysis was carried out using the non-parametric Wilcoxon signed-rank test with p<0.05 considered as significant. Results The mean values showed a significant decrease in the height of the vertical jump (-12,1%, p<0.001), an significant increase in the overstretching time phase, that is, the eccentric loading phase (p<0.001) following the performance of an incremental shuttle run; a temporal increase was observed in the isometric stabilization phase when the subject terminates the jump after landing, but statistics did not find the change to be significant. The mean value of maximal aerobic velocity reached by the sample in the Léger test was 13.0±0.5 km/h; equal to a VO2 max of 57,0 ml/kg/min. Discussion During the vertical jump, the athlete reproduces all the patterns of neuromuscular activation that can be found during characteristic sports movements, like breaking, cutting, acceleration and landing after the execution of a jump (Sannicandro, 2008). The analysis of some phases of the jump demonstrate the considerable influence that fatigue has upon the ability of the athlete to elevate the body and, above all, upon the duration of the extremely important phase of pushing. Alterations to the usual execution pattern of the jumping movement and, in particular, to the eccentric phase of the jump, could be put compared to slight decreases in postural control and consequently represent a potential risk of joint injury in the lower limbs.